Barriers and Assistance for Female Leaders in Academic STEM in the US - Laura McCullough (MDPI AG, 2020)
Women in science, technology, engineering, and mathematics (STEM) fields are under-represented, and women are also less likely than men to be in leadership positions, generally. Little is known about the intersection of these areas: women in leadership in STEM. To determine what sort of barriers and assistance female STEM leaders have encountered, a survey was developed asking women who are in academic leadership positions in STEM about their experiences. The main barriers were similar in the STEM area and in leadership: balancing work/home life, devaluing of achievements, and imposter syndrome. The main two types of assistance in both STEM and leadership were support from spouse/partner, and encouragement from peers. The main barriers women encounter are cultural and will take time to overcome. The main assistance women have had comes from people, not training or institutional structures.